Diffuse pancreatic cancer: Derivation for pancreatic gastrostomy - Farcic, Antonio; Delgado, Bolivar; Iraola, María L. (Cirugía del Uruguay, 1979)
The paper describes a case of pancreatic adenocarcinoma histologically corresponding to a diffuse infiltrating lobular carcinoma. Its macroscopic aspect was no clearly defined in operatory exploration and required extemporaneous biopsy, There follows a discussion of this procedure. Surgery consisted of pancreato-gastrostomy utilizing distal pancreatic section surface, with excellent results.